Serum Creatinine and Uric Acid Levels of Hypothyroid Patients (Bangladesh Journal of Medical Biochemistry, 2013)
Hypothyroidism is a clinical syndrome resulting from a deficiency of thyroid hormones which, in turn, results in a generalized slowing down of metabolic processes. It is associated with many biochemical abnormalities including increased serum creatinine and uric acid levels. We reviewed more than 30 articles and a good number of textbooks to evaluate serum creatinine and uric acid levels in hypothyroid patients. We found both these parameters are significantly higher in hypothyroid patients. Chronic kidney diseases (CKDs) also affect thyroid function in many ways leading to decreased T3 and T4. So, it is important for clinicians to differentiate between chronic kidney diseases and hypothyroidism with respect to their causal and consequential entities. DOI: http://dx.doi.org/10.3329/bjmb.v3i2.13814 Bangladesh J Med Biochem 2010; 3(2): 61-63